Er der en vej ud af islamofobien? - Om neoracismen og om en postkommunitaristisk antiracisme - Holm, Andreas Beck (Slagmark - Tidsskrift for idéhistorie, 2018)
Islamophobia is the predominant form of racism in Europe today. In this paper the logic and the origins of islamophobia are examined through the comparison of two major works on the subject, Etienne Balibar’s and Pierre-André Taguieff ’s analyses of European neoracism. Furthermore, these analyses also contribute to answering the questions why antiracist movements so far have been unable to stop islamophobia from spreading, and how antiracist strategy can be rearticulated. The paper argues that since contemporary racism, among other things, represents a communitarian reaction against globalization, antiracist strategy should attempt to reconquer the idea of community by focusing attention on the practical communities that – unlike the ideological communities of racism – are not only necessary for our lives together, but also unite people across the boundaries set up by racism.